A cross-sectional study examining the psychometric properties of the painDETECT measure in neuropathic pain - Cappelleri JC; Koduru V; Bienen EJ; Sadosky A (Journal of Pain Research, 2015)
Joseph C Cappelleri,1 Vijaya Koduru,2 E Jay Bienen,3 Alesia Sadosky41Pfizer Inc, Groton, CT, USA; 2Eliassen Group, New London, CT, USA; 3Outcomes Research Consultant, New York, NY, USA; 4Pfizer Inc, New York, NY, USABackground: Similarities and differences on the nine-item and seven-item versions of painDETECT, a patient-reported screener to identify neuropathic pain (NeP), have not been psychometrically explored across NeP conditions.Methods: Scores on the nine-item painDETECT (seven pain symptom items, one pain course pattern item, one pain radiation item) range from -1 to 38; scores ≥19 indicate NeP is likely (>90% probability). The seven-item version (only pain symptoms) score range is 0 to 35. painDETECT was administered to subjects with confirmed diagnoses of human immunodeficiency virus-related peripheral NeP (HIVP) (n=103), spinal cord injury-related NeP (SCI) (n=103), small fiber neuropathy (n=100), painful diabetic peripheral neuropathy (n=112), posttrauma/postsurgical NeP (n=100), and NeP in chronic low back pain (n=106) identified during office visits to US community-based physicians. Analysis of covariance compared mean scores (adjusted for age, sex, race, ethnicity, time since NeP diagnosis, and number of comorbidities) on the nine-item and seven-item versions of painDETECT. Cronbach's alpha assessed internal consistency reliability, and corrected item-to-total correlations assessed item-level discrimination.Results: The adjusted mean nine-item scores ranged from 21.0 (SCI) to 24.3 (small fiber neuropathy). Differences between conditions were either trivial or small-to-medium in magnitude. Cronbach's alpha gave overall internal consistency reliability of 0.76, with a range of 0.63 (SCI) to 0.82 (HIVP). Mean scores and Cronbach's alphas for the seven-item version were generally similar to the nine-item version. Corrected item-to-total correlations adequately discriminated all pain symptom items on both painDETECT versions for each condition (0.3–0.7), but the two nonsensory items on the nine-item version showed lackluster discrimination (<0.3).Conclusion: painDETECT scores were within the range indicating high probability of NeP. Differences between conditions were generally modest or not large. Both versions showed evidence of internal consistency reliability and item-level discrimination, suggesting that painDETECT is a useful screening measure for identifying NeP across NeP conditions.Keywords: painful diabetic neuropathy, spinal cord injury, back pain, small fiber neuropathy, HIV-related peripheral neuropathy, posttrauma neuropathy